Gallo - Díaz Huerta, Antonio; Frade, Sergio (Frida Films S.L., 2018)
Gallo lost his sight in a fateful accident while he was surfing. He was 39 years old. Far from giving up, he went back to surfing again and in 2016 he has won the World Adaptive Surfing Championship. Gallo wants to prove that people with disabilities can take any challenge they set themselves, and he will face one of the most difficult and dangerous challenges of his life: surfing a big wave. To succeed in his adventure, Gallo will have to prepare himself both physically and men- tally, but above all else he will have to overcome the doubts and fears of having to relive the accident that left him blind. --